Cover Image. Issue 8 (30th July 2018) - Turner, Paul J.; Feeney, Mary; Meyer, Rosan; Perkin, Michael R.; Fox, Adam T.
Abstract : The cover image, by Paul Turner et al., is based on the Editorial Implementing primary prevention of food allergy in infants: New BSACI guidance published, https://doi.org/10.1111/cea.13218 .